Mechanochromic luminescent behavior in hydrogen bonded liquid-crystalline complex. (11th February 2017) - Kondo, Mizuho; Hashimoto, Mayuko; Miura, Seiya; Kawatsuki, Nobuhiro
ABSTRACT: Mechanochromic luminescence (MCL) is an isothermal change in solid-state photolumienscent (PL) color in response to mechanical stimuli. In this work, we synthesized a novel acidic dopoant for pyridine terminated MCL compound to form suitable intermolecular interactions in the complex, and explored the PL properties of the acid and luminophore complex. The complex changed its fluorescence and diffusion spectrum, and these changes reverted their initial states upon heating above their melting point, revealing the acid complex changed its PL properties with maintaining machanoresponsive behavior.